Subverting Male Gaze: Mediterranean Women in Contemporary Croatian Cinema - Borjan, Etami (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2023)
This article intends to explore how female filmmakers in Croatia have represented social transformation in the Mediterranean during the last twenty years, and how gender issues have shaped Mediterranean narratives and characters. Thus, dominant representations of Mediterranean women, femininity and gender relations in recent Croatian women’s cinema will be critically reviewed. This work traces articulations of gender issues in contemporary women-centric films set on Croatia’s Adriatic coast. The majority of films shot by female directors in the last decade were set in Mediterranean cities, or small villages, where gender roles are strictly defined by a conservative society in which women’s roles are reduced to domestic space. However, contemporary Croatian women directors subvert this paradigm by presenting active, problem-solving female heroes that both challenge and deconstruct traditional roles imposed upon Mediterranean women. Croatian women filmmakers take us away from the idyllic Mediterranean scenery and stress its confining nature. The settings are deeply anti-exotic, deviating drastically from the appealing tourist image of the Mediterranean coast in presenting the oppressive roles which women there are forced to take. Physical space speaks loudly for its protagonists, and these spaces often mirror the trauma of their female inhabitants. Recent films contest the historic domination imposed on women by patriarchy and tradition, which have always undermined the advancement of female characters. Women filmmakers speak openly about female sexuality, not neglecting body and pleasure, but they try to subvert the male gaze by de-eroticizing nudity and sexual intercourse.